“What is our actual impact?”: A mixed-method assessment of a Belgian shelter for homeless men - Helleputte, Coralie; Nyssens, Marthe; Périlleux, Anaïs (Evaluation and program planning, 2025)
This paper presents an outcomes assessment carried out in an 84-bed long-term shelter for homeless men in Brussels. In the context of increasing Housing First studies, it investigates an instance of the traditional “treatment first” model and provides a new Belgian case study. Adopting a multidimensional approach, it aims to better understand what impact an average stay in a long-term shelter has on its residents. The assessment investigated several outcomes—income and housing, physical and mental health, life skills, social and assistance network—and relied on a participative mixed-method design. Although the shelter mission is broad and ambitious (i.e. autonomy, global well-being and reintegration into society), the assessment results show that the shelter struggles to have positive effects on the residents beyond the provision of basic care (a roof, food, administrative support) and that the stress felt by the residents even tends to increase during their stay. Several recommendations collectively emerged from the assessment: individualizing shelter support and making it evolve during the stay, reducing the size of the shelter while at the same time fostering community living, developing partnerships. At the public policy level, we would recommend revising the mission of long-term shelters in accordance with their means. •An outcomes assessment was carried out in an 84-bed long-term shelter for homeless men in Brussels.•Several dimensions are investigated (income, housing, health, skills, network) through a participative mixed-method design.•The results show that the shelter struggles to have positive effects on the residents beyond the provision of basic care.•The stress felt by the residents even tends to increase during their stay.•Several recommendations collectively emerged from the assessment.